Modulating Glypican4 Suppresses Tumorigenicity of Embryonic Stem Cells While Preserving Self‐Renewal and Pluripotency12. (20th August 2012) - Fico, Annalisa; De Chevigny, Antoine; Egea, Joaquim; Bösl, Michael R.; Cremer, Harold; Maina, Flavio; Dono, Rosanna
Abstract: Self‐renewal and differentiation of stem cell depend on a dynamic interplay of cell‐extrinsic and ‐intrinsic regulators. However, how stem cells perceive the right amount of signal and at the right time to undergo a precise developmental program remains poorly understood. The cell surface proteins Glypicans act as gatekeepers of environmental signals to modulate their perception by target cells. Here, we show that one of these, Glypican4 (Gpc4), is specifically required to maintain the self‐renewal potential of mouse embryonic stem cells (ESCs) and to fine tune cell lineage commitment. Notably, Gpc4 ‐mutant ESCs contribute to all embryonic cell lineages when injected in blastocyts but lose their intrinsic tumorigenic properties after implantation into nude mice. Therefore, our molecular and functional studies reveal that Gpc4 maintains distinct stemness features. Moreover, we provide evidence that self‐renewal and lineage commitment of different stem cell types is fine tuned by Gpc4 activity by showing that Gpc4 is required for the maintenance of adult neural stem cell fate in vivo. Mechanistically, Gpc4 regulates self‐renewal of ESCs by modulating Wnt/β‐catenin signaling activities. Thus, our findings establish that Gpc4 acts at the interface of extrinsic and intrinsic signal regulation to fine tune stem cell fate. Moreover, the ability to uncouple pluripotent stem cell differentiation from tumorigenic potential makes Gpc4 as a promising target for cell‐based regenerative therapies. Stem Cells 2012;30:1863–1874